The efficacy of sequentially comprehensive treatment based on surgery in the treatment of keloids: a retrospective study - Yang, Kun; Shi, Mengdong; Li, Shubo; Sun, Jianning; Huo, Ran; Fu, Cong (Frontiers in Medicine, 2025)
PurposeThe objective of this study is to investigate the clinical efficacy of sequentially comprehensive treatment based on surgery and to furnish clinical evidence for the management of keloids.Patients and methodsThe patients with keloids were retrospectively analyzed who underwent surgery-based sequentially comprehensive treatment at the Plastic Surgery Department of Shandong Provincial Hospital from January 2018 to August 2021. The recurrence rate and incidence of adverse reactions were explored for all the included patients. For patients who were followed up for more than 1 year, the clinical response rate was calculated, and the chi-square test was used to analyze which factors could influence clinical effectiveness. Binary logistic analysis was performed on the factors with statistical differences. For patients with a follow-up time of less than 1-year, paired t-test was used to evaluate their Vancouver Scar Scale (VSS) before and after treatment.ResultsA total of 67 patients with 80 keloids were included. The clinical response rate was 81.5% (44/54), the recurrence rate was 15.0% (12/80) and the adverse reaction rate was 4.5% (3/67). The clinical response rate of tumor-type keloids (95.8%) was higher than that of inflammatory-type (70.0%) with a significant difference (P = 0.040). After treatment, the color, blood vessel distribution, softness, thickness, and VSS score were all decreased, and the difference was statistically significant (P < 0.001).ConclusionThe sequentially comprehensive treatment based on surgery has a significant curative effect, as well as a low recurrence rate and a low adverse effect rate. The type of keloid has a statistically significant effect on clinical efficacy, and tumor-type keloids are more suitable for sequentially comprehensive treatment based on surgery.